Central Venous Access via Middle Approach Using the Seldinger Guidewire - Miguel Muñoz Cepero; Asiris García Almeida; Lisandra Muñoz López (Medisur)
Background: In recent years, venous access via middle approach with the technique described by English has been frequently used, leading to lower risk of pneumothorax and arterial puncture. In addition, it is easy to perform. Objective: to characterize the performance of central venous access via the middle approach to the internal jugular vein using the Seldinger guidewire in patients with hematologic diseases and/or anticoagulant therapy. Methods: a descriptive study was conducted from January to December 2009 in the Surgical Unit of the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos. Central venous access via middle approach using the technique described by English was performed in 47 patients suffering from hematologic diseases. Variables analysed were: number of attempts, indications and complications. Results: 43 central venous catheterizations were successful (91.48 %), 35 of them were achieved in the first attempt. The use of cytostatics was indicated in more than half of the cases (55.31 %). Complications were observed in 5 patients; arterial puncture was the most common (6.38 %). Conclusions: central venous access via the middle approach using the Seldinger guidewire is a suitable option for patients with hematologic diseases. It minimizes complications in patients treated with anticoagulants. In general, it is easily accessible and has a high success rate.